1993
DOI: 10.1016/0014-5793(93)81631-9
|View full text |Cite
|
Sign up to set email alerts
|

Function of saposin C in the reconstitution of glucosylceramidase by phosphatidylserine liposomes

Abstract: The function of saposin C (Sap C), a glucosylceramidase activator protein, in the enzyme stimulation by phosphatidylserine (PS) liposomes has been investigated. Using gel filtration experiments evidence was obtained for Sap C binding to PS large unilamellar vesicles (LUV) but not to glucosylceramidase. PS LUV, which by themselves are unable to tightly bind and stimulate the enzyme, acquire the capacity to also bind the enzyme after interaction with Sap C, making it express its full activity. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 25 publications
3
68
0
Order By: Relevance
“…Although sapC has the potential to solubilize membrane lipids (12,15), solution studies with liposomes have led to conflicting conclusions in assigning the GCase/sapC pair to either the ''solubilizer'' or the ''liftase'' mode of action (12,33). Our direct visualization of the events occurring at the membrane interface suggests that GCase hydrolyzes its substrate at the bilayer level with the help of sapC within a complex at the membrane surface.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although sapC has the potential to solubilize membrane lipids (12,15), solution studies with liposomes have led to conflicting conclusions in assigning the GCase/sapC pair to either the ''solubilizer'' or the ''liftase'' mode of action (12,33). Our direct visualization of the events occurring at the membrane interface suggests that GCase hydrolyzes its substrate at the bilayer level with the help of sapC within a complex at the membrane surface.…”
Section: Discussionmentioning
confidence: 90%
“…This is supported by the fact that sapC can increase the hydrolysis of soluble substrate analogs by up to 17-fold in the presence of large unilamellar vesicles (12,33). However, this activation cannot be explained by an increase in the accessibility of catalytic pocket, because the crystal structure of isolated GCase showed that the active site is easily accessible to solution compounds (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations